Nilai-Nilai dan Makna Gunungan Tradisi Sedekah Bumi di Dukuh Kenayan, Desa Karangmalang, Kabupaten Kudus dalam Pelestarian Budaya Jawa : (Kajian Etnolinguistik) - Anita Fitriani; Alif As-Syifatul Azizah; Imam Baehaqie (FKIP, Universitas Palangka Raya, 2026)
Indonesia is a country with a highly complex level of diversity, reflected in the uniqueness of culture found in each region. Culture represents a way of life that develops within society and is passed down from generation to generation through customs, language, art, beliefs, values, and moral principles that shape the identity and characteristics of a community. One form of Javanese cultural heritage is the Sedekah Bumi tradition, which serves as an expression of gratitude for the blessings and abundance provided by the earth. This tradition also symbolizes harmony among humans, nature, and God, and is generally carried out after the harvest season. In Kudus Regency, particularly in Karangmalang Village, the Sedekah Bumi tradition continues to be preserved as an important part of community life. Through agricultural parades and various cultural activities, this tradition strengthens social unity, maintains environmental balance, and conveys philosophical and social meanings. This study aims to examine the cultural values and meanings contained in the Sedekah Bumi tradition as an effort to preserve Javanese cultural richness.